Photoluminescence behavior in MgTiO3 powders with vacancy/distorted clusters and octahedral tilting - Ferri, E. A. V.; Sczancoski, J. C.; Cavalcante, L. S.; Paris, E. C.; Espinosa, J. W. M. [UNESP]; de Figueiredo, A. T. [UNESP]; Pizani, P. S.; Mastelaro, V. R.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V. Sa, 2009)
MgTiO3 powders were prepared by the complex polymerization method and heat treated at different temperatures for 2 h. These powders were analyzed by X-ray diffraction (XRD), Rietveld refinements, micro-Raman (MR) spectroscopy, X-ray absorption near edge spectroscopy (XANES), ultraviolet-visible (UV-vis) absorption spectroscopy and photoluminescence (PL) measurements. XRD patterns and MR spectra showed that the crystalline powders have a rhombohedral structure. XANES spectra indicated that the local structure of crystalline MgTiO3 powders is composed only by [TiO6] clusters, while the disordered exhibit the simultaneous presence of both [TiO5]and [TiO6] complex clusters into the lattice. UV-vis spectra revealed different optical band gap values as a function of heat treatment temperature. This result can be an indicative of intermediary energy levels within the band gap of this material because of structural defects into the perovskite-type structure. PL behavior was attributed to the structural order-disorder and/or distortions on the [TiO6]-[TiO6] complex clusters. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: Optical materials; Chemical synthesis; XAFS; Luminescence